Delia Grace on food safety - Grace, Delia (International Food Policy Research Institute, 2014)
Delia Grace, Program Leader, ILRI, and A4NH, at the side event, "Food Safety: Options for Addressing a Growing Crisis." IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info